Crossover learning of gestures in two ideomotor apraxia patients: A single case experimental design study. Issue 4 (19th May 2017) - Shimizu, Daisuke; Tanemura, Rumi
ABSTRACT: Crossover learning may aid rehabilitation in patients with neurological disorders. Ideomotor apraxia (IMA) is a common sequela of left-brain damage that comprises a deficit in the ability to perform gestures to verbal commands or by imitation. This study elucidated whether crossover learning occurred in two post-stroke IMA patients without motor paralysis after gesture training approximately 2 months after stroke onset. We quantitatively analysed the therapeutic intervention history and investigated whether revised action occurred during gesture production. Treatment intervention was to examine how to influence improvement and generalisation of the ability to produce the gesture. This study used an alternating treatments single-subject design, and the intervention method was errorless learning. Results indicated crossover learning in both patients. Qualitative analysis indicated that revised action occurred during the gesture-production process in one patient and that there were two types of post-revised action gestures: correct and incorrect gestures. We also discovered that even when a comparably short time had elapsed since stroke onset, generalisation was difficult. Information transfer between the left and right hemispheres of the brain via commissural fibres is important in crossover learning. In conclusion, improvements in gesture-production skill should be made with reference to the left cerebral hemisphere disconnection hypothesis.